A Ciliary Protein EVC2/LIMBIN Plays a Critical Role in the Skull Base for Mid-Facial Development - Kulkarni, Anshul K.; Louie, Ke’ale W.; Yatabe, Marilia; Ruellas, Antonio Carlos de Oliveira; Mochida, Yoshiyuki; Cevidanes, Lucia H. S.; Mishina, Yuji; Zhang, Honghao (Frontiers in Physiology, 2018)
Ellis-van Creveld (EvC) syndrome is an autosomal recessive chondrodysplastic disorder. Affected patients present a wide spectrum of symptoms including short stature, postaxial polydactyly, and dental abnormalities. We previously disrupted Evc2, one of the causative genes for EvC syndrome, in mice using a neural crest-specific, Cre-mediated approach (i.e., P0-Cre, referred to as Evc2 P0 mutants). Despite the fact that P0-Cre predominantly targets the mid-facial region, we reported that many mid-facial defects identified in Evc2 global mutants are not present in Evc2 P0 mutants at postnatal day 8 (P8). In the current study, we used multiple Cre lines (P0-Cre and Wnt1-Cre, respectively), to specifically delete Evc2 in neural crest-derived tissues and compared the resulting mid-facial defects at multiple time points (P8 and P28, respectively). While both Cre lines indistinguishably targeted the mid-facial region, they differentially targeted the anterior portion of the skull base. By comprehensively analyzing the shapes of conditional mutant skulls, we detected differentially affected mid-facial defects in Evc2 P0 mutants and Evc2 Wnt1 mutants. Micro-CT analysis of the skull base further revealed that the Evc2 mutation leads to a differentially affected skull base, caused by premature closure of the intersphenoid synchondrosis (presphenoidal synchondrosis), which limited the elongation of the anterior skull base during the postnatal development of the skull. Given the importance of the skull base in mid-facial bone development, our results suggest that loss of function of Evc2 within the skull base secondarily leads to many aspects of the mid-facial defects developed by the EvC syndrome.